Far from the tree ebook - Benway, Robin (2017)
National Book Award Winner, PEN America Award Winner, and New York Times Bestseller! Perfect for fans of This Is Us, Robin Benway's beautiful interweaving story of three very different teenagers connected by blood explores the meaning of family in all its forms—how to find it, how to keep it, and how to love it. Being the middle child has its ups and downs. But for Grace, an only child who was adopted at birth, discovering that she is a middle child is a different ride altogether. After putting her own baby up for adoption, she goes looking for her biological family, including— Maya , her loudmouthed younger bio sister, who has a lot to say about their newfound family ties. Having grown up the snarky brunette in a house full of chipper redheads, she's quick to search for traces of herself among these not-quite-strangers. And when her adopted family's long-buried problems begin to explode to the surface, Maya can't help but wonder where exactly it is that she belongs. And Joaquin , their stoic older bio brother, who has no interest in bonding over their shared biological mother. After seventeen years in the foster care system, he's learned that there are no heroes, and secrets and fears are best kept close to the vest, where they can't hurt anyone but him. Don't miss this moving novel that addresses such important topics as adoption, teen pregnancy, and foster care.